Seeking and defining the 'special' in specialist mental health nursing: A theoretical construct. (3rd February 2017) - Santangelo, Peter; Procter, Nicholas; Fassett, Denise
Abstract: In the context of an enduring debate about the distinct identity of mental health nursing, this qualitative study explored the nature, scope and consequences of mental health nursing practice. Data for interpretation were generated through interviews with 36 mental health nurses, five of their clients and one health care colleague, each of whom were asked to speak in as much detail as possible about what they believe is special about mental health nursing and what had influenced them to arrive at this understanding. Using a constructivist grounded theory approach, the study generated a substantive theory of recovery‐focused mental health nursing expressed as ' Being in the here and now, side by side, co‐constructing care' . The study revealed that the distinct nature and identity of mental health nursing provides the foundation that primes and drives practice scope and consequences. Conceptual interpretations of the data emphasized the mental health nursing perspective of care as an acquired lens founded in nursing as a profession and enhanced by the relational interplay between the nurse and the client that facilitates the nurse to adopt recovery‐focused practices. This theoretical construct holds the potential to be the mediating connection between client and mental health nurse. By situating mental health nursing and its central role in practice as something co‐constructed, findings from this study can be expanded beyond the Australian context, particularly in terms of mental health nursing's distinct professional identity and practice.